Analysis of Antimicrobial Peptide Metabolome of Bacterial Endophyte Isolated From Traditionally Used Medicinal Plant Millettia pachycarpa Benth - Ngashangva, Ng; Mukherjee, Pulok; Sharma, K. Chandradev; Kalita, M. C.; Indira, Sarangthem (Frontiers in Microbiology, 2021)
The increasing prevalence of AMR has posed major health concerns worldwide, and the addition of new antimicrobial agents is diminishing due to overexploitation of plants and microbial resources. Therefore, alternative sources and new strategies are inevitable to find novel biomolecules to counter AMR and pandemic circumstances. An association of plants with microorganisms is one of the basic natural interactions that involve the exchange of biomolecules. Such a relationship might have prompted the host and microbes on their respective biochemical properties and metabolites production. Furthermore, the discovery of taxol and taxane from an endophytic fungus, Taxomyces andreanae from Taxus wallachiana has stimulated much research on endophytes from medicinal plants. Paenibacillus peoriae IBSD35 isolated from the stem of Millettia pachycarpa Benth. was revived from the stock. It is a rod shape, motile, gram-positive, neutralophilic, and endospore-forming bacteria. Bioactive molecules were purified from its culture broth using 70% ammonium sulphate and column chromatography techniques. The biomolecule was enriched to 151.72-fold at a yield percentage of 0.05. Peoriaerin II, a highly potent and broad-spectrum antimicrobial peptide was isolated. LC-MS sequencing revealed its N-terminal is methionine. It has 4 number of negatively charged residues (Asp + Glu) and a total number of 2 positively charged residues (Arg + Lys). Its molecular weight is 4685.13 Da. It is linked to an LC-MS/MS inferred biosynthetic gene cluster with an accession number A0A2S6P0H9, and a blastp has shown it is 82.4% similar to fusaricidin synthetase of Paenibacillus polymyxa SC2. The 3-D structure conformation of the BGC was predicted using SWISS-MODEL homology modeling. Therefore, combining both genomic and proteomic results obtained from the culture broth of P. peoriae IBSD35 associated with M. pachycarpa Benth. will substantially increase understanding of antimicrobial peptides and assist to uncover novel biological agents.